100 Differential Sex Response to Aspirin in Decreasing Aneurysm Rupture in Humans and Mice. (August 2016) - Chalouhi, Nohra; Starke, Robert M.; Correa, Tatiana; Jabbour, Pascal; Zanaty, Mario; Brown, Robert; Torner, James; Hasan, David M.
Abstract : INTRODUCTION: We previously found that aspirin decreases the risk of cerebral aneurysm (CA) rupture in humans. We aim to assess whether a sex differential exists in the response of human CAs to aspirin and confirm these observations in a mouse model of CA. METHODS: A nested case-control analysis from the International Study of Unruptured Intracranial Aneurysms (ISUIA) was performed to assess whether a sex differential exists in the response of human CAs to aspirin. A series of experiments were subsequently performed in a mouse model of CAs. Aneurysms were induced with hypertension and elastase injection into mice basal cisterns. RESULTS: Aspirin decreased the risk of aneurysm rupture in men significantly more than women in ISUIA. There was a significantly decreasing odds ratio (OR) for hemorrhage with the increasing use of aspirin in men (OR, 0.05; P = .0024) but not in women (OR, 0.46; P = .23). In mice, aspirin and cyclooxygenase-2 (COX-2) inhibitor did not affect CA formation but significantly decreased the incidence of rupture. The incidence of CA rupture was significantly lower in male vs female mice on aspirin. Gene expression analysis from cerebral arteries showed higher 15-PGDH levels in male mice. The rate of CA rupture was similar in male mice receiving aspirin and 15-hydroxyprostaglandin dehydrogenase (15-PGDH) inhibitor compared with females receiving aspirin and 15-PGDH agonist signaling a reversal of the sex-differential response to aspirin. Compared with superficial temporal arteries, female human CAs showed higher COX-2 levels and lower 15-PGDH levels. CONCLUSION: Aspirin decreases aneurysm rupture in humans and mice, in part, through COX-2 pathways. Evidence from animal and human studies suggests a consistent differential effect by sex. 15-PGDH activation in females reduces the incidence of rupture and eliminates the sex-differential response to aspirin.